The Use of Wireless and Bed Alarm System Technology to Prevent The Risk of Falling Patients - Dwi Nopriyanto; Muhammad Aminuddin; Rita Puspa Sari (Fakultas Kedokteran, 2022)
Assessment of services provided in hospitals is not only based on patient satisfaction but must be able to protect patients as service users. Prevention of injury due to falls is one of the six indicators of patient safety while receiving services at the hospital. The purpose of this paper is to explore the use and examine the use of information technology applications to control the occurrence of falls during hospitalization. The literature used is taken from articles and journals related to the application of information technology in the world of health and nursing and non-health ranging from 2007-2019. Wireless devices offer additional patient monitoring capabilities, thereby increasing monitoring effectiveness with regard to changes in patient sleep status and increasing the alertness of all member care team members. One of the technological designs that can be applied is to use wireless technology and an alarm system in bed (wireless and bed alarm system).Keywords: Patient safety, prevention of fall injuries, use of technology.